2020
DOI: 10.1002/adsc.202000603
|View full text |Cite
|
Sign up to set email alerts
|

Hydroboration of Enynes and Mechanistic Insights

Abstract: Organoboron compounds have found broad applications in the construction of novel CÀ C, CÀ O, and CÀ N bonds via transition metal-catalyzed reactions. The hydroboration of CÀ C multiple bonds is one of the most important methodologies to introduce the boron atom into the organic skeleton. Traditionally, boranes were employed in the hydroboration of enynes under transition metal-free conditions. When precious metal catalysts, such as palladium and rhodium were employed in the reactions, the scope of the hydrobor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 115 publications
0
22
0
Order By: Relevance
“…Although a few previously published reviews summarize the hydroboration of unsaturated compounds, none of them dealt with selective alkyne hydroboration to provide a synthetically useful compound alkenylboron compounds. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Few review reports are also available which summarize the hydroelementation of olefins with specific catalysts [7,14,16,[18][19][20]22,24] or specific substrates, [12] however, the reviews are too limited to a certain subject and touch very small area of monoselective hydroboration of alkynes. Based on our observations, over the past few decades, regio-and stereoselective overview of alkyne hydroboration is a much-discussed topic.…”
Section: His Principal Research Interests Include the Development Of ...mentioning
confidence: 99%
“…Although a few previously published reviews summarize the hydroboration of unsaturated compounds, none of them dealt with selective alkyne hydroboration to provide a synthetically useful compound alkenylboron compounds. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Few review reports are also available which summarize the hydroelementation of olefins with specific catalysts [7,14,16,[18][19][20]22,24] or specific substrates, [12] however, the reviews are too limited to a certain subject and touch very small area of monoselective hydroboration of alkynes. Based on our observations, over the past few decades, regio-and stereoselective overview of alkyne hydroboration is a much-discussed topic.…”
Section: His Principal Research Interests Include the Development Of ...mentioning
confidence: 99%
“…Alternative, metal-free borylation reactions can provide milder conditions. Frustrated Lewis pair (FLP)-catalyzed C–H borylation and photoinduced ,,, borylation reactions represent another powerful recent development to install boron atoms into organic molecules. Borylation reactions employing heterogeneous catalysts have also attracted attention. However, despite these advances, transition metal-catalyzed borylation can be considered to be the most efficient method to synthesize organoboron compounds. Over the past few decades, numerous homogeneous catalytic borylation reactions have been developed .…”
Section: Introductionmentioning
confidence: 99%
“…The hydroboration of monoalkynes furnishing important alkenylborane building blocks is well established in the literature and has been discussed in several reviews. 1,2,4,7,10,12,48 Hydroboration of conjugated and separated diynes, because of the increased complexity of their structure, is much more challenging in the case of selectivity control. Moreover, the possibility for carrying out mono-, bishydroboration, polyaddition reactions and cyclisation reactions with these reagents creates the possibility to obtain various products, which have been used in the synthesis of natural compounds, pharmaceuticals (e.g., anticancer rizoxin D, cytotoxic nannocystin Ax, ivorenolides), [111][112][113][114][115][116][117][118][119] dyes, 120 p-conjugated compounds, or heterocycles.…”
Section: Hydroborationmentioning
confidence: 99%
“…Taniguchi et al reported another type of hydroboration of benzo [3,4]cyclo-dec-3-ene-1,5-diynes 144a-m which, following a borylative radical cyclisation, permitted the formation of 5-borylated 6,7,8,9-tetra-hydrobenzo[a]azulenes products 145a-m. 143,144 The boryl radicals were formed from N-heterocyclic carbene-boranes 146 with radical initiators, of which ditert-butyl hyponitrite (TBHN) 147 was the most effective. The homolytic bond dissociation energies of N-heterocyclic carbene boranes are much lower than those which possess typical boryl hydrides, and therefore these compounds might be used as precursors for rather stable boryl radicals 148.…”
Section: Hydroboration Of Separated 1n-diynesmentioning
confidence: 99%